Reliability of Frail and Barthel Tests for Detecting Frailty in Palliative Oncological Patients in a Home Hospitalization Unit: A Comparative Study - Susana León-Ramón; Emmanuel Navarro-Flores; Marta Elena Losa-Iglesias; Ricardo Becerro-de-Bengoa-Vallejo; Ana María Jiménez-Cebrián; Carlos Romero-Morales; Patricia Palomo-López; Daniel López-López (Life, 2022)
Cancer is a condition that can increase the risk of frailty. In addition, palliative oncological patients in home hospitalization can find their activities of daily living affected. The main objective was to measure the degree of frailty in the oncological population in home hospitalization comparing Barthel and Frail-VIG Indexes. This is a descriptive cross-sectional study. A sample of oncological patients in home hospitalization (n = 50) that included 27 men and 23 women were recruited, and disability due to frailty was measured using the VIG frailty index and the Barthel scale for Activities of Daily Living (ADLs). Spearman’s correlation coefficients were categorized as weak (rs ≤ 0.40), moderate (0.41 ≤ rs ≥ 0.69) or robust (0.70 ≤ rs ≥ 1.00), with a strong indirect correlation between the domains using the toilet, transferring and wandering on the Frail-VIG scale with an r (s) value −0.810 (p < 0.001), −0.831 (p < 0.001) and −0.805 (p < 0.001), respectively, and a moderate indirect correlation for the domains of eating −0.718 (p < 0.001), dressing −0.770 (p < 0.001) and urination −0.704 (<0.001). The Frail-VIG index above 0.35 points, that is, from moderate to severe, does not affect ADLs except in the nutritional dimension in a palliative oncological population in home hospitalization. The preliminary outcomes obtained should be considered to determine the impact of nutritional status with regard to ADLs in palliative oncological patients in a home hospitalization unit.